Towards a Better Understanding of the Ḥarsusi Language. (22nd February 2023) - Rubin, Aaron D
Abstract: The Ḥarsusi texts collected by T.M. Johnstone and published by Harry Stroomer (2004) comprise the only corpus of Ḥarsusi texts published to date, and thus remain an invaluable source for the study of that language. A re-examination of the audio recordings of these texts reveal that the draft manuscripts on which the published edition was based contain numerous discrepancies, including many errors. By using these audio recordings in order to obtain corrected readings, we are able to better analyse and more accurately describe the phonology and morphology of Ḥarsusi, a language for which we as yet have no comprehensive description.